Cultivation of Tilapia (Oreochromis niloticus) using the silvofishery method in Tanjungrejo, Percut Sei Tuan, North Sumatra Province - Elfiati, Deni; Susetya, Ipanna Enggar; Delvian; Rambey, Ridahati; Fadhilah, Amanatul (Talenta Publisher, 2021)
Silvofishery is a mangrove ecosystem management model that combines fisheries and forestry aspects. This method is also a solution for cultivators to cultivate fish without damaging the mangrove ecosystem. It is hoped that the results of this service activity can be used as a model or input for the community in order to manage ponds with silvofishery technology without having to do open ponds which will slowly damage the environment. This community service activity aimed to provide information and skills to partner groups on the silvofishery method. Other aim was to assist partners in the tilapia rearing process. Based on the description of the problems and objectives of this community service activity, the activities that have been carried out are counseling about silvofishery. The second activity, provision of tilapia seeds and feed for fish rearing activities in silvofishery ponds. The results obtained were increased partners' knowledge and skills regarding silvofishery. The people of Tanjungrejo Village also get tilapia cultivation products that can be traded without cutting down mangrove trees.